Material and Digital Reconstruction of Fragmentary Dead Sea Scrolls The Case of 4Q418a - Ben-Dov, Jonathan (Brill, 2022)
Scholars working with ancient scrolls seek ways to extract maximum information from the multitude of fragments. Various methods were applied to that end on the Dead Sea Scrolls as well as on other ancient texts. The present book augments these methods to a full-scale protocol, while adapting them to a new computerized environment. Fundamental methodological issues are illuminated as part of the discussion, and the potential margin of error is provided on an empirical basis, as practiced in the sciences. The method is then exemplified with regard to the scroll 4Q418a, a copy of a wisdom composition from Qumran.